Effect of ancillary (aminomethyl)phenolate ligand on efficacy of aluminum-catalyzed glucose dehydration to 5-hydroxymethylfurfural. (15th July 2018) - Saang'onyo, Daudi; Parkin, Sean; Ladipo, Folami T.
Graphical abstract: Modification of (aminomethyl)phenolate ligand (L R ) furnished L R AlMe2 complexes that efficiently catalyze glucose dehydration to 5-hydroxymethylfurfural in ionic liquids. In [BMIM]Br at 120 °C, L ph AlMe2 (2e ) produced HMF with 63%. Abstract: Air-stable dimethylaluminum complexes L R AlMe2 that contain (aminomethyl)phenolate (L R ) ligands were prepared in high yield. NMR data and X-ray crystallographic characterization of the molecular structures of several of the complexes confirmed bidentate coordination of the (aminomethyl)phenolate ligand to aluminum. Efficient aluminum catalysts for glucose dehydration to HMF were generated via modification of the (aminomethyl)phenolate ligand. L R AlMe2 complexes containing bidentate (aminomethyl)phenolate ligands with an aryl substituent on the amino moiety are efficient catalysts for glucose dehydration to HMF in ionic liquid solvents. In [EMIM]Br and [BMIM]Br, the reaction proceeds at 120 °C to very high conversion in 2 h to produce HMF with 60–63% selectivity and in 58–60% yield. Evidently, L R AlMe2 complexes catalyze glucose isomerization to fructose at ≥120 °C while the HMF yield depends on the degree of competing HMF loss to humins formation. These results indicate that additional studies of ancillary ligand effects on aluminum-catalyzed glucose dehydration are needed to improve knowledge of structure–function relationships that are key to increasing the efficiency of aluminum catalysts for dehydration of glucose (and ultimately cellulose) to HMF.